Part II—Clinical presentation, electrophysiologic characteristics, and when and how to ablate atriofascicular pathways and long and short decrementally conducting accessory pathways. (16th October 2019) - Soares Correa, Frederico; Lokhandwala, Yash; Cruz Filho, Fernando; Sánchez‐Quintana, Damián; Mori, Shumpei; Anderson, Robert H.; Wellens, Hein J. J.; Back Sternick, Eduardo
Abstract: Recognition of the presence, location, and properties of unusual accessory pathways for atrioventricular conduction is an exciting, frequently difficult, challenge for the clinical cardiac arrhythmologist. In this second part of our series of reviews relative to this topic, we discuss the steps required to achieve the correct diagnosis and appropriate management in patients with the so‐called "Mahaim" variants of pre‐excitation. We indicate that, nowadays, it is recognized that these abnormal rhythms are manifest because of the presence of atriofascicular pathways. These anatomical substrates, however, need to be distinguished from the other long and short accessory pathways which produce decremental atrioventricular conduction. The atriofascicular pathways, along with the long decrementally conducting pathways, have their atrial components located within the vestibule of the tricuspid valve. The short decremental pathways, in contrast, can originate in the vestibules of either the mitral or tricuspid valves. As a starting point, careful analysis of the 12‐lead electrocardiogram, taken during both sinus rhythm and tachycardias, should precede any investigation in the catheterization room. When assessing the patient in the electrophysiological laboratory, the use of programmed electrical stimulation from different intracardiac locations, combined with entrainment technique and activation mapping, should permit the establishment of the properties of the accessory pathways, and localization of its proximal and distal ends. This should provide the answer to the question "is the pathway incorporated into the circuit underlying the clinical tachycardia". That information is essential for decision‐making with regard to need, and localization of the proper site, for catheter ablation.